Press under Pressure: Framing of the Russian-Ukrainian Conflict in the Slovak Press - Andrej Habiňák (Communication Today, 2025)
Theories of media effects represent a key area of ​​research within media and communication studies that deals with the way media contents influence the cognitive, affective and behavioural responses of individuals, as well as their wider social and cultural impacts on society. Fundamental theories include agenda-setting, framing and priming. These theories provide a comprehensive framework for understanding the powerful effects of the media on the formation of public opinion, social norms, and political processes, emphasising the critical importance of readers’ media literacy. The present study primarily focuses on framing. It represents a key concept in the field of communication and media studies, which describes how the way information is presented can influence an audience’s perception and decision-making. This article examines different dimensions of framing, including its use in print media informing about the ongoing war in Ukraine, and analyses to what extent framing can be considered a manipulative tool. Through the analysis of media theory in this area and Slovak print media, this article provides certain insight on framing as a phenomenon that plays a fundamental role in the formation of public opinion and explores its potential linguistic and ethical implications. In conclusion, the author proposes concepts that could help minimise the risk of the manipulative use of framing.